Awareness Regarding Human Papilloma Virus and Its Vaccine Among Final Year MBBS Students - Sanghavi, Mithun M (National Journal of Community Medicine, 2014)
Background and Objectives: Human papilloma virus is the major cause of cervical cancer in women and HPV vaccination is emerging as the most effective option. As the medical students will serve the community in the future, awareness regarding HPV vaccine is very necessary among them. The current study seeks to assess the awareness regarding various aspects of HPV infection and its vaccine among medical students. Methods: A Cross sectional study was conducted in November 2013 at Shree M P Shah Government Medical College, Jamnagar. Total 160 students of final year M.B.B.S. were included in the study. Data regarding HPV and its vaccine were collected by using pretested semi structured questionnaire by interview technique. Results: None of the students knew the correct incidence and mortality of cervical cancer in India. More proportion of students stated sex workers (37.50%), women having multiple sexual partners (16.88%) and young sexually active women (18.75%) as a high risk group for HPV. 89.37% of the students stated cervical cancer caused by HPV. 23.75% of the medical students did not know regarding availability of HPV vaccine. The awareness regarding dosage and age schedule, side effects, contraindication, storage temperature, cost, efficacy etc. was lacking in majority of them. Conclusion: The level of awareness about HPV and HPV vaccine was low and gaps in knowledge existed among medical students. There is need to accelerate efforts of more focused and integrated teaching strategy regarding various aspects of HPV and its vaccine.